2022
DOI: 10.1149/1945-7111/ac741f
|View full text |Cite
|
Sign up to set email alerts
|

Review—Recent Advancements in Dye-Sensitized Solar Cells; From Photoelectrode to Counter Electrode

Abstract: Dye-sensitized solar cells (DSSCs) are promising photovoltaic technology with diverse indoor and outdoor applications. DSSCs can be integrated with curtains and glasses to power various devices, including wireless sensors, computer network peripherals, internet-of-things (IoT) devices, and wearable electronics. DSSCs have the potential to become the future source of energy. However, their efficiency, stability, and industrial production still need to be scaled up. The present review encompasses these elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 173 publications
1
17
0
Order By: Relevance
“…[22][23][24][25][26][27] The Internet of Things (IoT) market is emerging exceptionally and demands high amounts of off-grid low power consumption or selfpowered devices. 22,[28][29][30][31][32] Interestingly, recent studies have shown that emerging photovoltaic technologies such as perovskite solar cells (PSCs), [33][34][35] OSCs, 25,28,36 and dye-sensitized solar cells (DSSCs) [37][38][39] are better for converting indoor light into electricity than other inorganic Si, CIGS technologies. [40][41][42] This is due to a broader range of optical tunability, a higher absorption coefficient, and smaller leakage currents at low light intensities.…”
Section: Hemraj Dahiyamentioning
confidence: 99%
“…[22][23][24][25][26][27] The Internet of Things (IoT) market is emerging exceptionally and demands high amounts of off-grid low power consumption or selfpowered devices. 22,[28][29][30][31][32] Interestingly, recent studies have shown that emerging photovoltaic technologies such as perovskite solar cells (PSCs), [33][34][35] OSCs, 25,28,36 and dye-sensitized solar cells (DSSCs) [37][38][39] are better for converting indoor light into electricity than other inorganic Si, CIGS technologies. [40][41][42] This is due to a broader range of optical tunability, a higher absorption coefficient, and smaller leakage currents at low light intensities.…”
Section: Hemraj Dahiyamentioning
confidence: 99%
“…3 The selection of electrode materials significantly impacts the efficiency and stability of DSSCs. 5,6 The cost, brittleness, and limited light absorption capabilities of conventional electrodes like FTO or ITO are their drawbacks. As a result, scientists have been looking into alternative materials to improve DSSC performance.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The photoelectrode in a conventional DSSC is typically made of mesoporous TiO 2 . 9,10 However other materials have been explored in the literature, such as ZnO, Nb 2 O 5 , and semiconductor perovskites, in order to obtain a higher open-circuit voltage V oc . 11–15…”
Section: Introductionmentioning
confidence: 99%